The evaluation of work engagement among generation Z that involved in logistics business organizations in Selangor - Choo, Cai Xuan; Lai, Pei Qi; Ling, Hui Li (2023)
The senior workforce will soon be replaced as the most prevalent generation by Generation Z, who will make up more than a third of the global population. This research will examine the evaluation of work engagement among generation Z that involved in logistics business organizations. Therefore, this study aimed to analyse the relationship between work engagement and independent variables including job characteristics, organizational culture, teamwork and top management support by using Social Exchange Theory. In addition, quantitative research was undertaken by collecting data via questionnaire survey form which send it to be targeted respondents. The quantitative research has analysed by using the Multiple Linear Regression Analysis, Pearson Correlation Analysis and Reliability Analysis. As a result, the analysis has shown that the significance relationship between the work engagement and independent variables